(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The advent of mobile technologies has ushered in a new era for language education, giving rise to Mobile-Assisted Language Learning (MALL). This article explores the transformative potential of MALL, examining how smartphones and tablets, along with their associated applications, are reshaping language acquisition. It delves into the theoretical underpinnings of MALL, explores diverse applications in language learning, and highlights the benefits it offers, including increased accessibility, personalized learning, and enhanced engagement. While acknowledging the inherent challenges, such as the digital divide and the need for robust teacher training, this article emphasizes that with thoughtful implementation and ongoing research, MALL holds the key to unlocking more effective, equitable, and engaging language learning experiences for all.